China’s 21st Century Financial Foreign Policy - Gorodnia, N. (Китаєзнавчі дослідження, 2011)
The paper focuses on the main trends of China’s financial foreign policy in early 21st century in the areas of foreign currency reserves accumulation, investing capitals abroad, participation in global economic and financial institutions, and yuan internationalization, as well as the policy transition under the impact of the 2008-2009 global financial and economic crisis.